2021
DOI: 10.3390/biomedicines9010034
|View full text |Cite
|
Sign up to set email alerts
|

Shared Blood Transcriptomic Signatures between Alzheimer’s Disease and Diabetes Mellitus

Abstract: Alzheimer’s disease (AD) and diabetes mellitus (DM) are known to have a shared molecular mechanism. We aimed to identify shared blood transcriptomic signatures between AD and DM. Blood expression datasets for each disease were combined and a co-expression network was used to construct modules consisting of genes with similar expression patterns. For each module, a gene regulatory network based on gene expression and protein-protein interactions was established to identify hub genes. We selected one module, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 59 publications
(60 reference statements)
0
25
0
Order By: Relevance
“…At present, there are no reports about these two TFs and PE. GTF2B is one of the ubiquitous TFs required for transcription initiation, and it has been reported to be closely related to Alzheimer’s disease and type 2 diabetes ( Lee and Lee, 2021 ). The CCAAT/enhancer binding protein CEBPB belongs to a family of leucine-zipper TFs that participate in physiological processes such as energy metabolism, cell proliferation, and differentiation ( Huang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…At present, there are no reports about these two TFs and PE. GTF2B is one of the ubiquitous TFs required for transcription initiation, and it has been reported to be closely related to Alzheimer’s disease and type 2 diabetes ( Lee and Lee, 2021 ). The CCAAT/enhancer binding protein CEBPB belongs to a family of leucine-zipper TFs that participate in physiological processes such as energy metabolism, cell proliferation, and differentiation ( Huang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study [ 23 ] suggested that analyzing numerous gene expression datasets could cause a considerable amount of transcript information (due to the different platforms used for measuring gene expression) and trait-related signature data (due to the different phenotypical or disease statuses among the individual datasets) loss. Therefore, a MetaQC method that provides a score for the quality of the gene expression datasets for the meta-analysis [ 24 ] was used to enable the selection of high-quality blood gene expression datasets, which were then used for feature selection.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study used the TFs obtained from TRANSFACT [ 33 ] to predict blood AD cases among the different cohorts [ 30 ]. In addition, the updated TF catalog by Lambert et al [ 34 ] was used to identify the shared upstream blood genes between AD and diabetes [ 23 ]. Based on these studies, we implemented the TF list that had been manually updated by Lambert et al [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial dysfunction is involved in the onset and progression of neurodegenerative diseases [ 61 , 62 , 63 , 64 ]. It is therefore likely that the beneficial effects of BFT administration on mitochondrial function is not restricted to the activation of the ThDP-dependent enzyme complexes PDHC and OGDHC.…”
Section: Properties and Mechanism Of Action Of Benfotiaminementioning
confidence: 99%